Progesterone Increases Nicotine Withdrawal and Anxiety in Male but Not Female Smokers During Brief Abstinence. Issue 12 (17th June 2022) - Novick, Andrew M; Duffy, Korrina A; Johnson, Rachel L; Sammel, Mary D; Cao, Wen; Strasser, Andrew A; Sofuoglu, Mehmet; Kuzma, Alexandra; Loughead, James; Epperson, C Neill
Abstract: Introduction: Although exogenous progesterone may hold promise as a treatment for nicotine use disorders, it is unclear whether it is similarly effective in males and females. This study examined the effects of progesterone on nicotine use disorder comprehensively using behavioral, psychological, and neural measures in male and female smokers exposed to brief abstinence. Aims and Methods: Thirty-three male and 33 female non-treatment-seeking smokers participated in a double-blind, randomized, placebo-controlled crossover study of 200 mg of progesterone or placebo daily over a four-day abstinence period. Smoking behavior and subjective effects of nicotine were assessed at baseline and after final drug administration. Nicotine withdrawal, smoking urges, mood states, and neural response to smoking cues were measured at baseline, after the first drug administration, and after the final drug administration. Results: No main effect of drug (progesterone vs. placebo) emerged for any outcome. Significant sex by drug interactions emerged for nicotine withdrawal ( p = .020), perceived strength of nicotine ( p = .040), and perceived bad effects of nicotine ( p = .029). Males receiving progesterone reported worse nicotine withdrawal ( p = .046) and a trend towards decreased bad effects of nicotine ( p = .070). Males on progesterone also reported greater tension and anxiety relative to placebo ( p = .021). Females on progesterone perceived nicotine's effects as being stronger relative to placebo ( p = .046). Conclusions: Progesterone causes sex-dependent effects on smoking-related outcomes during brief abstinence. Specifically, progesterone in males may increase rather than decrease nicotine withdrawal and negative affect during abstinence, potentially hindering efforts to quit smoking. Implications: In male and female smokers undergoing a brief period of abstinence, we examined the effects of progesterone on smoking outcomes. While progesterone had limited effects in female smokers, in males, it worsened nicotine withdrawal and negative affect. Our findings emphasize the importance of analyzing sex differences in future studies examining progesterone as a potential treatment and suggest that progesterone in males could potentially exacerbate aspects of nicotine dependence. Clinicaltrials.gov registration: NCT01954966. https://clinicaltrials.gov/ct2/show/NCT01954966